PEMBIMBINGAN DAN PELATIHAN GURU MADRASAH TSANAWIYAH OLEH PENGAWAS MADRASAH DI KABUPATEN CIANJUR - Suryadi, Rudi Ahmad (Dirasa Islamiyya: Journal of Islamic Studies, 2022)
Teacher competence must be improved. One of the supports for improving the quality of teachers is the teacher mentoring and training program. This program is prepared by the madrasa supervisor. Teacher guidance and training is one of the strategic supervisory programs in accordance with the main functions of the Minister of Religion Regulation Number 2 of 2012 concerning Madrasah Supervisors and Islamic Teaching Supervisors. This paper aimed to describe the teacher mentoring and training program at Madrasah Tsanawiyah (MTs). By tracing several madrasah and confirming madrasah supervisors, it finded several training materials and models developed by madrasah supervisors, especially at the MTs level. The research used a qualitative approach. The method used is descriptive. Data were collected through observation (instruments), interviews, and documentation. The instrument is in accordance with the criteria developed in the madrasa supervisor's work guide. The research findings are that the mentoring and training program is one of the main functions of madrasah supervisors. At the Ministry of Religious Affairs of Cianjur, madrasah supervisors have carried out the preparation of teacher mentoring and training programs. The program was in accordance with the work guidelines set by the Ministry of Religious Affair and also paid attention to other supervisory regulations. There are 12 MTs supervisors in Cianjur who have developed a teacher mentoring and training program. The program contains the background, targets, goals, patterns, and materials for teacher guidance and training.